OPTIMIZATION AND SIMULATIONS OF POWER SYSTEM STABILITY FACTS CONTROLLERS COORDINATED WITH POWER SYSTEM STABILIZER BASED-TIME DELAY - Aibangbee, Johnson O. (FUDMA JOURNAL OF SCIENCES, 2026)
Transmission time-delays in electrical power grid significantly causes adverse effect on performance of control systems and can lead to system failure. The study analyzes the simultaneous tuning of the power system stabilizer (PSS) and power system stability FACTS controller coordinated static synchronous series compensator (SSSC). The proposes controller was designed and optimized using combine grasshopper optimization algorithm (GOA) with fuzzy proportional-integral-derivative (F-PID) controllers to effectively fine-tuned control parameters to minimize the impact of time delay signals. Simulation conducted using MATLAB R2016a environment with simultaneous calculation of the objective functions. Results obtained from proposes GOA optimized controller with different loading conditions, disturbances and variations in signal transmission delays were compared with those of differential evolution (DE), genetic algorithm (GA) and Whale optimization algorithm (WOA). Results proved that in single machine infinite bus (SMIB) system, GOA provides superior damping oscillations, reduced peak deviation, reaches steady state faster and provide lowest values in terms of integral of time-weighted absolute error (ITAE), lower percentage overshoot, and faster settling times of 0.00206 and 2.65 seconds, compared to DE, GA and WOA of 0.00337, 0.00219, 4.00 sec; 0.00318 0.00223, 3.35 sec; and 0.002905 0.00105 and 3.34 sec. whereas, for multi-machine system, the ITAE values with GOA is 0.0001806 compared to DE, GA, and WOA of 0.0002084,0.0002007,and 0.0001832. The proposed GOA optimized controller reduced the objective function values by 16.29% better than WOA (14.53%), GA (14.53%), and DE (13.69%), in the SMIB system and 1.43%, 9.95%, and 13.33%, for the multi-machine systems.